Antimicrobial activities and neuroprotective potential for Alzheimer's disease of pure, Mn, Co, and Al-doped ZnO ultra-small nanoparticles - ULLAH, IMRAN; Neder, Reinhard; Ahmad, Mushtaq; Khan, Abdul Qadir; Rauf, Abdur; Alshammari, Abdulrahman; Albekairi, Norah Abdullah (Green Processing and Synthesis, 2024)
The current research aimed to gain insights into the synthesis, characterization, and biomedical applications of ultra-small (US) zinc oxide (ZnO) and manganese (Mn), cobalt (Co), aluminum (Al)-doped ZnO nanoparticles (NPs). These NPs were synthesized using the sol-gel method and treated with various organic ligand molecules, serving as surface modifiers and stabilizers. The influence of ligand molecules on the growth kinetics was observed by monitoring the synthesis time until gel formation, which revealed that the ligand molecules significantly slowed down gelation. Moreover, the shape and final size of NPs were also analyzed. X-ray diffraction (XRD) confirmed single-phase crystallization in all samples. Ultraviolet-visible (UV-Vis) spectroscopy revealed a broad absorbance peak in the range of 347-355 nm. Tauc's method estimated an optical bandgap of 3.1-3.16 eV. Infrared Fourier transform (FT-IR) spectroscopy corroborated the formation of ZnO NPs decorated with various functional groups. Structural studies were performed using DISCUS software, where all necessary parameters were refined, and suggested a crystallite/NP size in the range of 3-10 nm. The citrate molecule (cit), a capping agent, exhibits the smallest crystallite/NPs. The samples were explored for antimicrobial and anti-acetylcholinesterase enzyme (AChE) activities. Among all samples, only 3-5% Mn-doped ZnO with acetate (ac) molecules as ligands showed antimicrobial activities at different concentrations. Moreover, 3% and 5% Co-doped ZnO with ac, and 3% Co-doped ZnO with dimethyl-l-tartrate (dmlt) and cit, were also active at various concentrations against Gram-positive bacteria, methicillin-resistant Staphylococcus aureus (MRSA), and Bacillus cereus (BC). The highest zone of inhibition of 7.5 ± 0.2 mm against MRSA and 10.0 mm for BC were observed. The lowest zone of inhibition was reported as 3.25 ± 0.25 mm against MRSA and 3.0 mm against BC. A direct relationship between the zone of inhibition and the concentration was observed. ZnO NPs inhibit 87.39 ± 0.002% AChE, while 3% Al-doped, 3 and 5% Co-doped NPs inhibit 78.8 ± 0.017%, 56.2 ± 0.002%, and 62.7 ± 0.051% AChE, respectively. An intermediate response of AChE inhibition was observed: 42.0 ± 0.018% for 3% Mn-doped NPs and 32.6 ± 0.0034% for 5% Mn-doped NPs. Various strategies were employed to further optimize their activities.
CRIS-Team Scopus Importer:2025-02-04
Keywords: anti-AChE; antimicrobial; doped ZnO; sol-gel; US-NPs